Identification of a Novel ENU-Induced Mutation in Mouse Tbx1 Linked to Human DiGeorge Syndrome - Jiaofeng Chen; Xue Zhang; Jie Li; Chenmeng Song; Yichang Jia; Wei Xiong (Neural Plasticity)
The patients with DiGeorge syndrome (DGS), caused by deletion containing dozens of genes in chromosome 22, often carry cardiovascular problem and hearing loss associated with chronic otitis media. Inside the deletion region, a transcription factor TBX1 was highly suspected. Furthermore, similar DGS phenotypes were found in the Tbx1 heterozygous knockout mice. Using ENU-induced mutagenesis and G1 dominant screening strategy, here we identified a nonsynonymous mutation p.W118R in T-box of TBX1, the DNA binding domain for transcription activity. The mutant mice showed deficiency of inner ear functions, including head tossing and circling, plus increased hearing threshold determined by audiometry. Therefore, our result further confirms the pathogenic basis of Tbx1 in DGS, points out the crucial role of DNA binding activity of TBX1 for the ear function, and provides additional animal model for studying the DGS disease mechanisms.